PENGUATAN KOMPETENSI KEWIRAUSAHAAN MELALUI PELATIHAN PENYUSUNAN PROPOSAL BISNIS BAGI SISWA SMA DHARMA BHAKTI PALEMBANG - Faradila Meirisa; Charisma Ayu Pramudhita (Marsialapari: Jurnal Pengabdian Kepada Masyarakat, 2026)
Entrepreneurship is an essential competency that should be developed at the secondary education level to enhance students’ independence and readiness to face future economic challenges. This community service program aimed to strengthen the entrepreneurial competencies of students at SMA Dharma Bhakti Palembang through business proposal preparation training. The program employed a participatory training approach consisting of lectures, interactive discussions, business proposal development practice, and mentoring sessions. The training materials covered business opportunity identification, market analysis, marketing strategies, operational planning, and simple financial projections. The results showed that participants were able to prepare business proposals more systematically and gained a better understanding of business planning aspects. Furthermore, the training improved students’ ability to identify business opportunities, analyze market potential, and develop appropriate business strategies. It also increased participants’ motivation, self-confidence, and interest in entrepreneurship. Therefore, the program effectively strengthened students’ entrepreneurial competencies and provided practical learning experiences in business planning..